2022
DOI: 10.1002/pon.6030
|View full text |Cite
|
Sign up to set email alerts
|

Financial toxicity and mental well‐being of the oral cancer survivors residing in a developing country in the era of COVID 19 pandemic – A cross‐sectional study

Abstract: Objectives The primary outcome measures evaluated the financial toxicity and mental well‐being of the oral cancer survivors. Methods A cross‐sectional study of oral cancer survivors who were disease‐free for more than 6 months after treatment and visited the hospital for a routine follow‐up is included in the study. Mental well‐being and financial toxicity were evaluated using the Depression, Anxiety, and Stress Scale ‐ 21 (DASS 21) and Comprehensive Score for financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…And secondly, a systematic review demonstrated relatively clear associations exist between FT and stress, spiritual suffering, fear of recurrence, and overall psychological symptoms [48]. Numerous studies also found positive associations between increases in FT and higher levels of depression and anxiety [49,50]. It is not controversial to say that this in turn affect physical symptoms such as sleep disturbance and fatigue, and ultimately result in inferior life quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And secondly, a systematic review demonstrated relatively clear associations exist between FT and stress, spiritual suffering, fear of recurrence, and overall psychological symptoms [48]. Numerous studies also found positive associations between increases in FT and higher levels of depression and anxiety [49,50]. It is not controversial to say that this in turn affect physical symptoms such as sleep disturbance and fatigue, and ultimately result in inferior life quality.…”
Section: Discussionmentioning
confidence: 99%
“…And each item was given on a Likert-type format with 5 options (1 = none of the time, 5 = all of the time). The total score ranges from 10 to 50, with the following stages: none (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), mild (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), moderate (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and severe (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Wu and Jiang translated it into Chinese with satisfactory internal consistency coe cient (Cronbach's α = 0.91) [38].…”
Section: Self-perceived Burden Scale (Spbs)mentioning
confidence: 99%
“…Papers in this Special Issue also draw important attention to the interconnections among mental, physical and social determinants of health. Thaduria et al 16 report on the association between financial toxicity, employment and well-being in oral cancer survivors in a sub-Himalayan city in North India in the era of Covid-19. In a systematic review of the duration of time from symptom onset to the first consultation with a health professional in breast cancer patients, Petrova et al 17 demonstrated the role that literacy and education, stigma, low socioeconomic status and social support play in delaying help-seeking in this population.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%
“…Papers in this Special Issue also draw important attention to the interconnections among mental, physical and social determinants of health. Thaduria et al 16 . report on the association between financial toxicity, employment and well‐being in oral cancer survivors in a sub‐Himalayan city in North India in the era of Covid‐19.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%
See 1 more Smart Citation